Public Self and Structural Stigma as Predictors of Help Seeking Behaviour in Mental Health and Organizational Management - Ali, Fausan; Zaidan, Muhammad; Ahmad, Azkar (Journal Social Humanity Perspective, 2024)
This paper examines the correlation between mental stigma and help-seeking behaviour in the context of organisations making it a psychological and managerial problem. The quantitative research design allowed the author to identify 400 adult participants and collect the data based on a stratified random sampling method. Examples of dimensions of stigma and their impact on urge to seek help were measured via the help seeking questionnaires like the Stigma Scale in yet to receive help (SSRPH), the Self-Stigma in the need to seek help (SSOSH) and the General Help-Seeking Questionnaire (GHSQ). Data analysis applied descriptive statistics, correlation, and multiple regression in defining the predictors of help-seeking behaviour. The results show that the public stigma and self-stigma both greatly decrease the contamination of help-seeking intentions but that self-stigma has the greater negative impact. These findings demonstrate not only the importance of stigma as an individual level psychological barrier, but also reveal its role as high-priority management issues on an organizational level involving organizational well-being and productivity and organizational culture. Theoretically, the research is a contribution because it rearranges the idea of stigma as a management issue enshrined in organizational constructs, management approach, and employment culture. In practice, it would require organizations to incorporate stigma reduction policies within the human resource practices, leadership education and the employee support frameworks. With mental health stigma as a moral and strategic necessity, organizations are empowered to create healthier environments to flourish through resilience, engagement and performance. The paper also proposes cross sector approaches and culturally sensitive practices to institutionalize stigma reduction into long term organizational practice.